Evaluation of Prostate specific antigen levels and its correlation with histopathological findings - Pudasaini, Sujata; Subedi, Neeraj; Shrestha, Nagesh Mani (Journal of Pathology of Nepal, 2019)
Background: Prostate specific antigen is a tumor marker though is expressed by both normal and neoplastic prostate tissue. The absolute value of Prostate specific antigen is useful for determining the extent of prostate cancer and its treatment. Prostate specific antigen also increases in cases like Benign Prostatic Hyperplasia and prostatitis. The availability of Prostate specific antigen as a marker has encouraged its use to diagnose both cancer and cancer recurrences. Materials and methods: This is a cross sectional study conducted in a tertiary hospital over a period of two years. Cases of prostatic disease undergoing surgery during the study period were taken. Prostate specific antigen level of all these cases were correlated with clinical and histopathological findings. Results: A total of 51 cases of prostatic disease underwent surgery during the study period with the mean age of 66.57 ± 10.68 years. On histopathological examination, 70.6% had benign prostatic hyperplasia and 17.6% had prostatic adenocarcinoma. Prostate specific antigen level was <4 ng/ml in 45.1% cases and >20.1ng/ml in 15.7%. In case of carcinoma prostate, 88.9% had prostate specific antigen level > 20.1ng/ml and 11.1% had prostate specific antigen level in a range of 10.1- 20 ng/ml. In case of chronic prostatitis, 66.7% had prostate specific antigen level in a range of 4.1-10 ng/ml. However, in case of high grade prostatic intraepithelial neoplasia (HGPIN), 66.7% had PSA level <4 ng/ml. Conclusions: Strong correlation of prostate specific antigen levels of > 20.1 ng/ml with carcinoma prostate was seen.